Growth Through the Therapeutic Element of Relationships: The Experience of a Women's Spirituality Program - Jerebic, Sara (Edinost in dialog, 2025)
The lives of modern women are characterized by the intertwining of the demands of work, family and social expectations, which increasingly leads to inner conflicts. In such a context, the ability to consciously pause, reflect inwardly and form self-help groups becomes crucial for the well-being of the individual and thus also for her family. Programs to promote women's spirituality, which vary according to culture and context, can be helpful in this regard. We present a study on the participation of women from Slovenia in a 90-day spiritual programme for women, focusing on the relational aspect. We used a semi-structured questionnaire survey and examined the experiences of the programme participants through content analysis. The results showed that relational support was a key factor that helped participants to go through personal change. The findings indicate a clear need for spiritual deepening and living presence in relationships and provide guidelines for the development of therapeutic and pastoral approaches to holistically support women in the modern world.